Oncolytic virotherapy for malignant glioma: translating laboratory insights into clinical practice - Auffinger, Brenda; Ahmed, Atique U.; Lesniak, Maciej S. (Frontiers in Oncology, 2013)
Glioblastoma multiforme, one of the most common and aggressive brain tumors in adults, is highly resistant to currently available therapies and often recurs. Due to its poor prognosis and difficult management, there is an urgent need for the development and translation of new anti-glioma therapeutic approaches into the clinic. In this context, oncolytic virotherapy arises as an exciting treatment option for glioma patients. These natural or genetically engineered viruses are able to effectively infect cancer cells, inducing a specific anti-tumor cytotoxic effect. In addition, some viruses have been redesigned to specially modulate glioma microenvironment, to express cytokines to boost a systemic anti-glioma immune response and to incorporate angiostatic genes to decrease glioma vasculature. Although recent clinical trials have confirmed the safety of oncolytic virotherapies in the brain, their moderate clinical efficacy has not yet matched the encouraging preclinical laboratory results. In this review, we will discuss the leading anti-glioma virotherapy approaches that are presently under preclinical and clinical evaluation. We will also review different delivery methods, in vivo virus behavior, fate, replication, and intratumoral spread, activation of antitumor immune response and targeting of glioma stem cells. We will focus on the advantages and limitations of each therapeutic approach and how to overcome these hurdles to effectively translate exciting laboratory results into promising clinical trials.